POTENSI UNGGULAN SUB-SEKTOR TANAMAN PERKEBUNAN DI KABUPATEN BANYUASIN - Helfa Septinar; Budi Utomo; Maharani Oktavia; Siti Asiyah; Nuranisa Nuranisa (Jurnal Sains Informasi Geografi (J SIG), 2022)
Banyuasin Regency is an area that has enormous agricultural potential. Plantation is part of agriculture which has an important role in the development of Banyuasin Regency. To optimize the development of the area, it is necessary to optimize its potential. The purpose of this research is to see what the leading sectors of the plantation are in Banyuasin Regency. The research location is in Banyuasin Regency, South Sumatra Province. This research was conducted for 6 months starting from March to August 2020. The research data is secondary data from BPS data from Banyuasin Regency and data from the plantation and livestock office of Banyuasin Regency. This research is a descriptive study with a quantitative approach. In this study, the data analysis method used is the Location Quotient (LQ) analysis method. The research results of superior plantations in Banyuasin Regency are three types of commodities, namely rubber, oil palm and coffee. Even though Banyuasin Regency has many excellent plantation potentials, there are plantations that do not have the potential to become the regional superiority, namely coconut.